InCIEC 2015 Proceedings of the International Civil and Infrastructure Engineering Conference - Yusoff, Marina; Abdul Hamid, Nor Hayati; Arshad, Mohd Fadzil; Arshad, Ahmad Kamil; Mohd Ridzuan, Ahmad Ruslan; Awang, Haryati; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
The special focus of these proceedings is on the areas of infrastructure engineering and sustainability management. They provide detailed information on innovative research developments in construction materials and structures, in addition to a compilation of interdisciplinary findings combining nano-materials and engineering. The coverage of cutting-edge infrastructure and sustainability issues in engineering includes earthquakes, bioremediation, synergistic management, timber engineering, flood management and intelligent transport systems.
Timber Engineering -- Concrete Waste and Earthquake Engineering -- Flood Management and Intelligence Development -- Fluvial And River Engineering Dynamics -- Transportation Systems, Infrastructure and Intelligent Transport -- Geotechnical Engineering -- Innovative Construction Materials & Structures -- Bioremediation and Engineering -- Synergistic Innovative Management -- Nano-Materials For Engineering.
Keywords: Civil engineering; Environmental engineering; Biotechnology; Bioremediation; Water; Hydrology; Building materials; Natural disasters; Civil Engineering; Environmental Engineering/Biotechnology.; Water; Structural Materials; Natural Hazards